A method of evaluating vehicle controllability according to the dynamic factor - Turenko, Anatoly; Podrygalo, Mikhail; Klets, Dmytro; Hatsko, Vasily; Barun, Marina (Eastern-European Journal of Enterprise Technologies, 2016)
The study has explored one of the most important performance properties of the vehicle, which determines road traffic safety, – control in a steady mode. A method has been suggested for evaluating the stability of a vehicle against yaw with regard to the dynamic factor. We have found a dependence of the dynamic factor on the design and operational parameters of the vehicle. The dynamic factor can be reduced through achieving a neutral steering of the vehicle by controlling the ratio of the total lateral rigidity of the tires of the front and rear wheels. It has been determined that a change in the tire air pressure, measured by the developed algorithm, improves vehicle stability against yawing and thus contributes to traffic safety. In the example of the truck Ural-4320, the suggested method was used to determine the total lateral stiffness of the wheels under the condition of ensuring the vehicle’s neutral steering. The study has revealed that in the case of an equipped vehicle it is necessary to reduce the tire pressure in the wheels on the equalizer trolley in correlation to the air pressure in the tires of the front wheels. The research results can be used both in operating the existing vehicles and for designing new ones.